2007
DOI: 10.1016/j.molcel.2007.02.016
|View full text |Cite
|
Sign up to set email alerts
|

Insights into Transcription Initiation and Termination from the Electron Microscopy Structure of Yeast RNA Polymerase III

Abstract: RNA polymerase III (RNAPIII) synthesizes tRNA, 5S RNA, U6 snRNA, and other small RNAs. The structure of yeast RNAPIII, determined at 17 A resolution by cryo-electron microscopy and single-particle analysis, reveals a hand-like shape typical of RNA polymerases. Compared to RNAPII, RNAPIII is characterized by a bulkier stalk and by prominent features extending from the DNA binding cleft. We attribute the latter primarily to five RNAPIII-specific subunits, present as two distinct subcomplexes (C82/C34/C31 and C53… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
85
1

Year Published

2007
2007
2014
2014

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(91 citation statements)
references
References 36 publications
5
85
1
Order By: Relevance
“…These experiments strongly suggest that termination and cleavage of the RNA precursor are not coupled in the RNAPIII transcription process. Consistent with its role in termination, structural analysis of RNA-PIII showed that the C37/C53 heterodimer is positioned at the outer end of the DNA-binding cleft, toward the front of the EC, allowing the complex to sense the incoming DNA (Fernandez-Tornero et al 2007).…”
Section: Rnapiii: a Terminator On Its Own?mentioning
confidence: 84%
“…These experiments strongly suggest that termination and cleavage of the RNA precursor are not coupled in the RNAPIII transcription process. Consistent with its role in termination, structural analysis of RNA-PIII showed that the C37/C53 heterodimer is positioned at the outer end of the DNA-binding cleft, toward the front of the EC, allowing the complex to sense the incoming DNA (Fernandez-Tornero et al 2007).…”
Section: Rnapiii: a Terminator On Its Own?mentioning
confidence: 84%
“…5), and TFIIF exerts a comparable effect in stabilizing the incorporation of a 5-nt RNA into a pol II heteroduplex DNA complex containing a 10-bp bubble (55). In addition to these functional similarities, TFIIF and the C53/C37 subcomplex appear to attach to similar sites on the second largest subunits of their respective RNA polymerases, the Rpb2/C128 lobe domains above the DNA binding cleft (11,48), and the stability of these interactions is also dependent on attachment of the respective paralogue Rpb9/C11 subunits to the lobe domain (7,8,56).…”
Section: Discussionmentioning
confidence: 97%
“…The ␤-hairpin and the two acidic residues at its tip are conserved in C11, and the acidic residues are essential for the intrinsic cleavage activity of pol III (8). Cryoelectron microscopy structural analysis of pol III (11) shows mass density compatible with the N-terminal zinc binding domain of C11, occupying a position on the C128 lobe domain of pol III that resembles the location of the N-terminal zinc binding domain of Rpb9 on Rpb2 in the structure of pol II (12). A mass corresponding to the C-terminal zinc binding domain of C11 was not observed in the pol III electron microscopic structure, but it has been suggested that this domain may bind to the pol III pore 1 (10).…”
mentioning
confidence: 99%
“…Discrepancies in the location of A49/34.5 and TFIIF may be explained by different locations of a related dimerization module on the two polymerases, or by the presence of additional, unrelated domains in both factors. Sequence analysis showed that A49/34.5 and TFIIF possibly have a counterpart in Pol III, the C37/53 heterodimer (not shown), which may occupy a similar location on the Pol III surface near the lobe and funnel (Fernandez-Tornero et al, 2007).…”
Section: A49 and A345 Form A Tfiif-like Heterodimer Near The Funnelmentioning
confidence: 99%
“…For Pol III, a 17 Å electron microscopy (EM) structure (Fernandez-Tornero et al, 2007) and a homology model for the core enzyme and the crystal structure of the C17/25 subcomplex are available (Jasiak et al, 2006) (for comparability, EM resolutions throughout this paper generally refer to a Fourier shell correlation (FSC) of 0.5). For Pol I, the overall shape and dimensions were first revealed by EM analysis of two-dimensional crystals (Schultz et al, 1993).…”
Section: Introductionmentioning
confidence: 99%